RATING PHARMACEUTICAL EQUIVALENCE in vitro BY HPLC METHODOLOGY FOUR DRUGS CONTAINING ACETAMINOPHEN, CHLORPHENIRAMINE MALEATE AND PHENYLEPHRINE HYDROCHLORIDE TABLETS - Samaniego Joaquin, Jhonnel (2016)
Pharmaceutical equivalence in vitro four medicines containing paracetamol, maleate chlorpheniramine and phenylephrine hydrochloride tablets using Chromatography Liquid High Resolution reversed phase (HPLC-RP) is called, the dissolution profiles of the reference product and were determined 4 products in the study also were established and compared the differences in the dissolution profiles of the reference product and the products under study. The design methodology was analytical, experimental and comparative. Four formulations marketed in Lima and the reference product was evaluated by the method of high performance liquid chromatography (HPLC). the dissolution profiles were measured and were compared using a statistical method independent model difference factor (f1) and similarity (f2), which revealed that the dissolution curves are different between products reference laboratory and laboratories analyzed, since f1 and f2 were outside the ranges established in two of the four formulations tested. The results showed that two of the four products tested by this method would not be pharmaceutical equivalents.